2005
DOI: 10.1002/hep.20665
|View full text |Cite
|
Sign up to set email alerts
|

Systemic infusion of angiotensin II exacerbates liver fibrosis in bile duct–ligated rats†

Abstract: Recent evidence indicates that the renin-angiotensin system (RAS) plays a major role in liver fibrosis. Here, we investigate whether the circulatory RAS, which is frequently activated in patients with chronic liver disease, contributes to fibrosis progression. To test this hypothesis, we increased circulatory angiotensin II (Ang II) levels in rats undergoing biliary fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
164
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 155 publications
(167 citation statements)
references
References 44 publications
(35 reference statements)
1
164
0
2
Order By: Relevance
“…AT-II increased TGF-ß gene expression in a dose-dependent manner in activated HSCs in vitro (20). We and others reported that suppression of AT-II by ACE-I markedly attenuated experimental liver fibrosis development and suppressed TGF-ß (3,20).…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…AT-II increased TGF-ß gene expression in a dose-dependent manner in activated HSCs in vitro (20). We and others reported that suppression of AT-II by ACE-I markedly attenuated experimental liver fibrosis development and suppressed TGF-ß (3,20).…”
Section: Introductionmentioning
confidence: 79%
“…The increased number of HSCs during liver fibrogenesis reflects the activity of several growth factors (1). Among the growth factors, transforming growth factor-ß (TGF-ß) and platelet-derived growth factor (PDGF) are key mediators in liver fibrogenesis (3,4). Liver fibrosis is characterized by the excessive deposition of extracellular matrix (ECM), which leads to a severe pathological disturbance in the liver.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in hepatic transforming growth factor β1 (TGF-β1) and pro-inflammatory cytokine levels was attenuated in AT1-R knockout mice compared to WT mice [11] . Furthermore, Bataller et al [12] demonstrated that increased systemic Angiotensin (Ang) II augments hepatic fibrosis and promotes inflammation, oxidative stress, and thrombogenic events. Telmisartan shows the greatest affinity for the AT1-R and exhibits the longest half-life of the ARBs that are currently available [13] .…”
Section: Introductionmentioning
confidence: 99%
“…The effects of Ang II on hepatic stellate cells (HSC) has been extensively studied (Bataller et al 2005(Bataller et al , 2003a(Bataller et al , b, 2000Wei et al 2001;Yokohama et al 2006;Zhang et al 2003), yet little information exists on the effect of Ang-(1-7) on these cells. Most studies using cell culture use culture medium supplemented with fetal calf serum (FCS) to encourage cell growth.…”
Section: Introductionmentioning
confidence: 99%